المرأة والثورة الحسينية (دورها الانساني والفكري والاعلامي) (Journal of the College of Basic Education, 2022)
In Islamic history extension several centuries, Muslim women have had a great role in standing by men and their participation in building, giving, changing, and reforming society. At the same time, it is a partner in assuming religious responsibility, as well as an active element in the development of Muslim society and its superiority to progress And progress, and can not do all this and the occurrence of any fundamental change in society without its existence. The revolution of Imam Hussein (peace be upon him) needs to explore the historical, moral, and social dimensions of this revolution because it has included distinguished personalities, who have sacrificed themselves and proved their worth in courage and patience for vice, and to defend the principles of Islam and reform the society of spoilers and tyrants in order to achieve justice and justice. these figures represented the summit of pride, sacrifice, and altruism including their attitudes and ideals unable to pen than described.It is worth mentioning that women have had a distinctive presence in the march Husseiniya since its inception and until the end of (the battle of Taf) the martyrdom of Imam Hussein (peace be upon him), because Imam Hussein (peace be upon him) realizes the need for the presence of women in this fair battle in order to play its role in raising awareness and counseling motivation to fight enemies and defend the principles of true Islam and also its role after the battle in educating the public and the delivery of the goals of Husseiniya revolution true to the world public opinion in various levels and correction of media disinformation inflicted on Imam Hussein (peace be upon him) by the junta Umayyad, claiming that he did not come out of the reparation but he wanted to be king.